Effect of ant-hills on the floristic richness of plant communities of a large depression in the Great Chaco - Lewis, Juan P (1991)
The effect of ant-hills of Camponotus punctulatus (Mayr.) on the floristic riebness of plant eommunities in the southem Chaco is analized. The ant-hills are conical mounds with an average height of 0.6 m and a diameter of 1.0 m. Ant-hills produce an inerease in quadrat floristic riehness, but in any given community a low percentage of species grow exclusively or preferentially on the ant-hill. Therefore the effeet of ant-bills over the floristic riebness of the community is less marked !han over the quadrat floristic richness. Ant-hill exclusives or preferential species are rarities, i.e. with less than 20 % constaney, in any community. Ant-hills provide refugia for species to grow in environments otherwise unsuitable for them.